Structural Study of the Apatite Nd 8 Sr 2 Si 6 O 26 by Laue Neutron Diffraction and Single-Crystal Raman Spectroscopy - An, Tao (2016)
A single-crystal structure determination of Nd8Sr2Si6O26 apatite, a prototype intermediate-temperature electrolyte for solid oxide fuel cells grown by the floating-zone method, was completed using the combination of Laue neutron diffraction and Raman spectroscopy. While neutron diffraction was in good agreement with P63/m symmetry, the possibility of P63 could not be convincingly excluded. This ambiguity was removed by the collection of orientation-dependent Raman spectra that could only be consistent with P63/m. The composition of Nd8Sr2Si6O26 was independently verified by powder X-ray diffraction in combination with electron probe microanalysis, with the latter confirming a homogeneous distribution of Sr and the absence of chemical zonation commonly observed in apatites. This comprehensive crystallochemical description of Nd8Sr2Si6O26 provides a baseline to quantify the efficacy of cation vacancies, oxygen superstoichiometry, and symmetry modification for promoting oxygen-ion mobility.